2-Bromo-N-(2-hy-droxy-5-methyl-phen-yl)-2-methyl-propanamide. (2011)
In the title mol-ecule, C(11)H(14)BrNO(2), there is twist between the mean plane of the amide group and the benzene ring [the C-N-C-C torsion angle is -172.1 (2)°]. The amide H atom forms an intra-molecular hydrogen bond with the Br atom. In the crystal, inter-molecular O-H⋯O and weak C-H⋯O hydrogen bonds link mol-ecules into a chain along [100].